Reviving Vavilov’s vision: The tragedy of biodiversity governance and principles for reform - David J. Bertioli; Soraya C. M. Leal-Bertioli; Tarikua Erda; Charles E. Simpson; Scott Barrett; Peter H. Raven (Proceedings of the National Academy of Sciences, 2025)
This perspective addresses two of humanity’s greatest challenges: feeding a growing population and conserving biodiversity. We begin by examining the legacy of Nikolai Vavilov, who pioneered the improvement of crops such as wheat and beans by hybridizing them with their wild relatives. This strategy used wild species biodiversity to introduce new genetic variation into crops, making them more resilient and productive. Its adoption around the world greatly increased food security and brought lasting benefits to humanity. However, since the 1990 s, well-intentioned laws shifted the governance of biodiversity from a shared global resource to the sovereign control of nation states, with serious unintended consequences. These changes have disrupted the collection, preservation, exchange, and use of biodiversity, all of which are central to Vavilov’s strategy for crop improvement and to biodiversity science more broadly. Efforts at reform have been frustrated as the issues became moralized, inhibiting the open dialogue needed for change. Using foundational concepts shared by science and good governance, we propose seven empirically grounded principles for reform, to help realign biodiversity governance with its intended aims. We then illustrate one possible framework—underpinned by global financing to protect biodiversity hotspots—that would align incentives and work in synergy with the principles to foster practical reform. The principles, together with frameworks that align incentives, would create the conditions for stronger biodiversity conservation and research, agricultural development, global food security, and all the associated benefits to humanity.